MAYBE Initial complexity problem: 1: T: (1, 1) f3(a, b) -> f1(a, b) (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] (?, 1) f1(a, b) -> f300(a, c) [ 0 >= a + 1 ] start location: f3 leaf cost: 0 Repeatedly removing leaves of the complexity graph in problem 1 produces the following problem: 2: T: (1, 1) f3(a, b) -> f1(a, b) (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a, b) with all transitions in problem 2, the following new transition is obtained: f3(a, b) -> f1(a + 1, b) [ a >= 0 ] We thus obtain the following problem: 3: T: (1, 2) f3(a, b) -> f1(a + 1, b) [ a >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 1, b) [ a >= 0 ] with all transitions in problem 3, the following new transition is obtained: f3(a, b) -> f1(a + 2, b) [ a >= 0 /\ a + 1 >= 0 ] We thus obtain the following problem: 4: T: (1, 3) f3(a, b) -> f1(a + 2, b) [ a >= 0 /\ a + 1 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 2, b) [ a >= 0 /\ a + 1 >= 0 ] with all transitions in problem 4, the following new transition is obtained: f3(a, b) -> f1(a + 3, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 ] We thus obtain the following problem: 5: T: (1, 4) f3(a, b) -> f1(a + 3, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 3, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 ] with all transitions in problem 5, the following new transition is obtained: f3(a, b) -> f1(a + 4, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 ] We thus obtain the following problem: 6: T: (1, 5) f3(a, b) -> f1(a + 4, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 4, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 ] with all transitions in problem 6, the following new transition is obtained: f3(a, b) -> f1(a + 5, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 ] We thus obtain the following problem: 7: T: (1, 6) f3(a, b) -> f1(a + 5, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 5, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 ] with all transitions in problem 7, the following new transition is obtained: f3(a, b) -> f1(a + 6, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 ] We thus obtain the following problem: 8: T: (1, 7) f3(a, b) -> f1(a + 6, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 6, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 ] with all transitions in problem 8, the following new transition is obtained: f3(a, b) -> f1(a + 7, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 ] We thus obtain the following problem: 9: T: (1, 8) f3(a, b) -> f1(a + 7, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 7, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 ] with all transitions in problem 9, the following new transition is obtained: f3(a, b) -> f1(a + 8, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 ] We thus obtain the following problem: 10: T: (1, 9) f3(a, b) -> f1(a + 8, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 8, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 ] with all transitions in problem 10, the following new transition is obtained: f3(a, b) -> f1(a + 9, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 ] We thus obtain the following problem: 11: T: (1, 10) f3(a, b) -> f1(a + 9, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 9, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 ] with all transitions in problem 11, the following new transition is obtained: f3(a, b) -> f1(a + 10, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 ] We thus obtain the following problem: 12: T: (1, 11) f3(a, b) -> f1(a + 10, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 10, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 ] with all transitions in problem 12, the following new transition is obtained: f3(a, b) -> f1(a + 11, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 ] We thus obtain the following problem: 13: T: (1, 12) f3(a, b) -> f1(a + 11, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 11, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 ] with all transitions in problem 13, the following new transition is obtained: f3(a, b) -> f1(a + 12, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 ] We thus obtain the following problem: 14: T: (1, 13) f3(a, b) -> f1(a + 12, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 12, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 ] with all transitions in problem 14, the following new transition is obtained: f3(a, b) -> f1(a + 13, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 /\ a + 12 >= 0 ] We thus obtain the following problem: 15: T: (1, 14) f3(a, b) -> f1(a + 13, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 /\ a + 12 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 13, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 /\ a + 12 >= 0 ] with all transitions in problem 15, the following new transition is obtained: f3(a, b) -> f1(a + 14, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 /\ a + 12 >= 0 /\ a + 13 >= 0 ] We thus obtain the following problem: 16: T: (1, 15) f3(a, b) -> f1(a + 14, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 /\ a + 12 >= 0 /\ a + 13 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 By chaining the transition f3(a, b) -> f1(a + 14, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 /\ a + 12 >= 0 /\ a + 13 >= 0 ] with all transitions in problem 16, the following new transition is obtained: f3(a, b) -> f1(a + 15, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 /\ a + 12 >= 0 /\ a + 13 >= 0 /\ a + 14 >= 0 ] We thus obtain the following problem: 17: T: (1, 16) f3(a, b) -> f1(a + 15, b) [ a >= 0 /\ a + 1 >= 0 /\ a + 2 >= 0 /\ a + 3 >= 0 /\ a + 4 >= 0 /\ a + 5 >= 0 /\ a + 6 >= 0 /\ a + 7 >= 0 /\ a + 8 >= 0 /\ a + 9 >= 0 /\ a + 10 >= 0 /\ a + 11 >= 0 /\ a + 12 >= 0 /\ a + 13 >= 0 /\ a + 14 >= 0 ] (?, 1) f1(a, b) -> f1(a + 1, b) [ a >= 0 ] start location: f3 leaf cost: 1 Complexity upper bound ? Time: 0.923 sec (SMT: 0.862 sec)